Paradigmas tecnológicos e estágios de diversificação tecnológica - de Lima Avanci, Vanessa; Urraca Ruiz, Ana (Estudios económicos, 2021)
This paper tests the existence of stages of technological diversification for a group of Asian and Latin-American countries since the late eighties; this is, when new technological paradigms emerged. Assuming that changes in technological specializations are linked to changes in productive specializations, this work look for evidences about the evolutions of technological structures in stages, this is, an initial phase of strong specialization in a few technical fields followed by a growing diversification, all along the period of expansion of techno-scientific paradigms. As the paradigms reduce their possibilities given the technological trajectories, technological opportunities become lower and U format-curve is expected. In general terms, countries reduced their technological distances with a wide reference area making more diversified their technological profiles. Nevertheless, different patterns of diversification/specialization were identified which must obey to other factors beyond the catching-up process. Among these factors, the role of technological leaders and transnational corporations is quite relevant.